The Social and Political Identities of the Shi'i Community in Lebanon - Rami Siklawi (Arab Studies Quarterly, 2014)
Since the early days of the Shi'i presence in Lebanon, the Shi'i community has been considered the most marginalized and underprivileged community. This had been the case of the Shi'ites during the Mamluk period, the Ottoman period, the French mandate period, and again during the post-independence period. This article addresses the Shi'ite presence in Lebanon until the eve of Lebanese Civil War (1975). The article will explore the various aspects of socio-political identities of the Shi'ites and how that changed and developed during the Ottoman period, the French mandate, and the independence period by elaborating on the main actors and processes/phases that shaped this change. It has been argued that the marginalization and the neglect policies that were applied against the Shi'ites opened the wide doors for the Shi'i community to migrate to the urban cities in Lebanon (mainly Beirut) starting from the late nineteenth and early twentieth century, and this had also been expanded to the rest of the world (mainly America and West Africa). This migration played a key role in developing their contemporary social and political identities in which Musa al-Sadr and his movement played an important part.